Rekomendasi Pemilihan Hotel Berbasis Chatbot dengan Framework Rasa Dengan Metode Natural Language Processing (NLP) - Oktavianita, Ryke Putri; Sutanto, Felix Andreas (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
This research discusses the development of a chatbot with the Framerowk Rasa platform which is integrated into the Telegram application to provide information about recommendations for selecting hotels in Semarang Regency. The aim is to make it easier for prospective hotel renters or tourists to find a hotel. In order to overcome this problem, artificial intelligence was developed in the form of a chatbot with a Natural Language Processing (NLP) approach. Chatbot technology enables more human and informative interactions with prospective hotel renters, helping them find hotels that match their preferences. By utilizing Natural Language Processing (NLP), chatbots can provide comprehensive information at any time, without being tied to operational hours or human presence. Apart from that, NLP also plays an important role in understanding human natural language and facilitating interactions between humans and machines. The Rasa framework, as an open source machine learning framework, provides the ability to build chatbots that understand human language and adapt to new data.